Exploring food security among recently resettled Syrian refugees: results from a qualitative study in two Canadian cities. Issue 4 (2nd November 2020) - Vatanparast, Hassan; Koc, Mustafa; Farag, Marwa; Garcea, Joseph; Engler-Stringer, Rachel; Qarmout, Tamer; Henry, Carol; Racine, Louise; White, Judy; Iqbal, Romaina; Khakpour, Mahasti; Dasarathi, Sindhuja; et al.
Abstract : Purpose: This study aims to provide a qualitative in-depth account of the status and experience of food insecurity for Syrian refugee households in Toronto and Saskatoon, Canada. The study considers the range of geographic, socio-economic, cultural and gendered components shaping and determining the barriers and management of food insecurity. Design/methodology/approach: The study included 54 semi-structured interviews with refugee families in Toronto and Saskatoon who resettled in Canada after November 2015. In addition, 15 semi-structured in-person or telephone interviews were conducted with settlement and support agencies to measure their capacity to respond to issues of food insecurity for Syrian refugees. Findings: Syrian refugees reported experiencing food insecurity as part of the broader resettlement journey, including in the transitional phase of refuge and in each settlement context in Canada. Income status in Canada was reported as a key barrier to food security. Low-income barriers to food security were experienced and shaped by factors including food affordability, physical access and availability and the extent of familial or other support networks including sponsorship relationships. Participants also reported how managing food insecurity contributed to the intensification of gender expectations. Originality/value: The analysis reveals food insecurity as both an income and non-income based concern for refugees during the process of resettlement. The study also highlights the importance of considering variations between primary barriers to food security identified by Syrian families and key informants as critical to the development of strategies designed to mitigate the impacts of resettlement on food security.